Contrasting effects of GPS device and harness attachment on adult survival of Lesser Black‐backed Gulls Larus fuscus and Great Skuas Stercorarius skua. (9th January 2016) - Thaxter, Chris B.; Ross‐Smith, Viola H.; Clark, Jacquie A.; Clark, Nigel A.; Conway, Greg J.; Masden, Elizabeth A.; Wade, Helen M.; Leat, Eliza H. K.; Gear, Sheila C.; Marsh, Mike; Booth, Chris; Furness, Robert W.; et al.
Abstract : Telemetry has become an important method for studying the biology and ecology of animals. However, the impact of tracking devices and their method of attachment on different species across multiple temporal scales has seldom been assessed. We compared the behavioural and demographic responses of two species of seabird, Lesser Black‐backed Gull Larus fuscus and Great Skua Stercorarius skua, to a GPS device attached using a crossover wing harness. We used telemetry information and monitoring of breeding colonies to compare birds equipped with a device and harness, and control birds without an attachment. We assessed whether tagged birds have lower short‐term breeding productivity or lower longer term overwinter return rates (indicative of overwinter survival) than controls. For Great Skua, we also assessed whether territory attendance within the breeding season differed between tagged and control birds. As with previous studies on Lesser Black‐backed Gull, we found no short‐term impacts on breeding productivity or long‐term impacts on overwinter return rates. For Great Skua, there was no evidence for impacts of the device and harness on territory attendance or breeding productivity. However, as found by a previous study of Great Skuas using a different (body) harness design, there was strong evidence of reduced overwinter return rates. Consequently, a device attached using a wing harness was considered suitable for long‐term deployment on Lesser Black‐backed Gulls, but not on Great Skuas. These findings will inform the planning of future tracking studies.